2014
DOI: 10.1002/da.22228
|View full text |Cite
|
Sign up to set email alerts
|

Data-Driven Course Trajectories in Primary Care Patients With Major Depressive Disorder

Abstract: The used data-driven approach provided a parsimonious and clinically informative way to describe course variation across MDD patients. Using the trajectory groups to investigate prognostic factors of MDD provided insight in potentially useful prognostic factors. Importantly, trajectory-group membership was itself a strong predictor of future mental well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
28
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 39 publications
(58 reference statements)
3
28
0
2
Order By: Relevance
“…A recent study showed differences in longer term outcomes based on MDD patients’ initial symptom trajectories in primary care (Wardenaar et al, 2014). The first year of assessment clarified patients’ trajectories, and 2 subsequent years’ data allowed outcome comparisons among trajectory groups: Patients with a “chronic” trajectory showed small improvements (year 1) but maintained elevated symptoms (year 2); “early remission” patients showed relatively quick and large symptom reductions (especially during the first 9 months of year 1) and maintained their improvements (year 2); “remission + recurrence” patients showed improvements but then deterioration (both during year 1) and elevated symptoms thereafter (year 2); and “late remission” patients showed slower improvements than early remission patients (year 1) that were largely maintained (year 2).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed differences in longer term outcomes based on MDD patients’ initial symptom trajectories in primary care (Wardenaar et al, 2014). The first year of assessment clarified patients’ trajectories, and 2 subsequent years’ data allowed outcome comparisons among trajectory groups: Patients with a “chronic” trajectory showed small improvements (year 1) but maintained elevated symptoms (year 2); “early remission” patients showed relatively quick and large symptom reductions (especially during the first 9 months of year 1) and maintained their improvements (year 2); “remission + recurrence” patients showed improvements but then deterioration (both during year 1) and elevated symptoms thereafter (year 2); and “late remission” patients showed slower improvements than early remission patients (year 1) that were largely maintained (year 2).…”
Section: Introductionmentioning
confidence: 99%
“…En la literatura internacional, la historia de depresión se ha asociado con una mayor recurrencia del cuadro 25 , observándose que la patología tiene un desarrollo crónico en un tercio de los pacientes deprimidos del nivel primario [26][27][28] , incrementando el riesgo de padecer un peor estado de salud y discapacidad funcional por períodos prolongados 25,29 .…”
Section: Discussionunclassified
“…También se detectó una frecuencia de riesgo suicida superior a 70%, cifra cercana a la reportada en hospitales comunitarios de la X región 24 , pero más alta que la señalada en el extranjero [31][32] . Estos indicadores de compromiso del cuadro clínico son predictores de mala respuesta y recurrencia/cronicidad 27,28,33,34 , y parecieran influirse recíprocamente en pacientes depresivos de APS 31,32 .…”
Section: Discussionunclassified
“…For example, one approach commonly used in prognosis studies of recurrent and long-term conditions presenting to primary care is for information on predictors (such as pain intensity) to be ascertained by mailed self-complete questionnaires, or personal interview and examination in research clinics several days after their index consultation (e.g. [8][9][10][11][12][13][14]). This approach offers several advantages, as it facilitates: 1) a wider range of predictor information to be collected than would be possible within the time-constrained primary care consultation, 2) greater standardisation of data collection procedures, 3) a "cooling off period" between being informed about the study at the point of care, and consenting to provide information on potential predictors that would not be considered part of routine care.…”
Section: Introductionmentioning
confidence: 99%